Alternations in markers of insulin resistance: HOMA-IR, HOMA-B, QUICKI, after dual therapy combination with delapril/manidipine in prediabetic hypertensive patients. (11th May 2022) - Liontos, A; Papathanasiou, A; Biros, D; Papagiannopoulos, C; Tsourlos, S; Athanasiou, L; Kolios, NG; Pappa, C; Veliani, C; Zarachi, A; Christaki, E; Liberopoulos, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose: The administration of the 30mg hydrochloric delapril and 10mg hydrochloric manidipine formulation is indicated for patients with idiopathic hypertension whose arterial pressure cannot be sufficiently managed with monotherapy. The purpose of this study is to investigate the effect of the premade combination delapril/manidipine 30/10mg per day on the variation of HOMA-IR, HOMA-B and QUICKI values, in patients with stage 2 hypertension (systolic blood pressure (SBP) 160-180 mmHg and/or diastolic blood pressure (DBP) 100-110 mmHg) and with prediabetes (IFG/IGT) before and after the 3-month treatment with the fixed combination dual-therapy. Methods: 53 patients (30 male/23 female, from whom 12 smokers and 7 alcohol users) who visited our outpatient clinic for lipid metabolism disorders and fulfilled the study's criteria joined the study's sample. They were randomized in the delapril/manidipine group. The patients' BMI was 28.73 [27.73-30.3] and the SBP and DBP values were: 156 [151-161] and 100 [88-101] mmHg respectively. Results: The resulting variations of SBP and DBP levels, as well as the variations of glucose and insulin levels and HOMA-IR, HOMA-B and QUICKI are presented on Table 1. Results: From the sampled patients it seems that the 3-month treatment with delapril/manidipine improved statistically significantly the levels of both SBP and DBP (reduction by -11.54% and -12% respectively, p<0.001 for both values). Glucose levels witnessed a 1.55% decrease with statistical significance while a notable increase in insulin by 4.65% was also observed after the 3-month treatment, albeit without any statistical significance. Concerning HOMA-IR and QUICKI, there were no significant variance, while HOMA-B values showed a statistically significant increase (7%, p=0.006)